Tick exposure and prevalence of Borrelia burgdorferi antibodies among hunters and other individuals exposed to vector ticks in eastern Poland - Anna Pańczuk; Małgorzata Tokarska-Rodak; Dorota Plewik; Justyna Paszkiewicz (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. Lyme borreliosis is the most frequent tick-borne disease in Europe and North America, and the number of registered cases is on the increase. Frequent presence in the habitats of ticks enhances the risk of tick bites and possible infection with Borrelia burgdorferi spirochetes. Objective. The aim of the study was to assess the risk of B. burgdorferi infection posed to hunters and other individuals exposed to activity-related contact with ticks. Material and methods. The study was carried out in the northern part of the Lublin Province (eastern Poland) and involved 150 individuals exposed to tick bites (110 hunters and 40 individuals exposed to activity-related contact with ticks). The analysis of sera for the presence of B. burgdorferi IgM and IgG antibodies was carried out. All 150 individuals were tested with the ELISA assay, and positive and borderline results of the assay were verified with the Western blot test. All study participants completed a questionnaire, which provided information about exposure to ticks, application of prophylactic measures, and awareness of Lyme borreliosis. Results. The ELISA assay revealed a positive or borderline result in at least one of the classes of B. burgdorferi antibodies in 63.3% (95/150) of the individuals (IgM 14.0%, IgG 63.3%). Verification carried out with the Western blot test showed a positive or borderline result in at least one of the antibody classes in 38.0% (57/150) of the examined persons (IgM 2.7%, IgG 36.7%). Abdomen (56.0%) and legs (53.7%) were the most frequently bitten body regions. Tick bites on the abdomen were significantly more frequently declared by hunters. Inspection of the body after returning from natural areas was more popular prophylactic method than use of repellents. Inspection of the body was significantly more often used in the group of the hunters. Conclusions. The risk of B. burgdorferi infection among hunters and other individuals undertaking activities associated with exposure to tick bites in the study area is high.